COI-5P gene sequence variation in Philippine Hydropuntia edulis (Gracilariaceae, Rhodophyta) [Research note] - Ferrer, Ma. Salvacion R.; Gomez, Rosalie N.; Dumilag, Richard V. (2020)
Hydropuntia edulisis an agar producing seaweed. In part due to its economic relevance, the last few decades have seen substantial efforts toward exploring its uses. With these developments, information on its genetic diversity is still, however, incipient. Here, phylogenetic and haplotype analyses in Philippine H. edulis were performed based on mtDNA COI-5P gene sequences. Using our newly generated dataset and previous accessions, the range of pairwise intra- and interspecific differences in H. edulis was determined. A total of 14 H. edulis haplotypes were recovered, of which seven were newly detected. Ten (10) haplotypes were found in the Philippines, eight of which appeared to be exclusive in the region. The genetic relationships in H. edulis as inferred from phylogenetic and haplotype network analyses did not follow a clear biogeographic structure. Future work will be necessary to explore the lack of detectable haplotype distribution pattern as presently found. This study can be seen as a fundamental point for future research on the management and conservation of H. edulis in the Philippines.